Transformative Translations? Challenges and tensions in territorial innovation governance - Völker, Thomas; Slaattelid, Rasmus; Strand, Roger (NOvation — Critical Studies of Innovation, 2023)
Since the 1990s, changing ways of producing and circulating knowledge have been accompanied by debates that diagnose and call for change in the relationship between science, society, politics, and innovation. Most recently in Europe, some of these debates emphasize the concept of responsible research and innovation (RRI). In this paper, we present a comparative analysis of different territorial RRI-pilots within the Horizon 2020-funded project TRANSFORM. In these pilots, different translations of RRI become visible. RRI (1) gets translated as participatory and deliberative modes of innovation governance aimed at transformative change, (2) takes the shape of citizen science projects; and (3) is enacted as participatory agenda setting and (plans for a) citizen assembly. We argue that it is the often-invisible work of establishing, nurturing, and caring for relationships within the territorial R&I ecosystems – what can the thought of as ongoing “maintenance work” – that creates the conditions for more responsive modes of innovation governance, and thus a shift towards transformative change in innovation policy. Through describing these translations and the related practices we will direct attention to the potential, challenges, and systemic barriers of this kind of work.